“To see or not to see: that is the question.” The “Protection-Against-Schizophrenia” (PaSZ) model: evidence from congenital blindness and visuo-cognitive aberrations - Landgraf, Steffen; Osterheider, Michael (Frontiers in Psychology, 2013)
The causes of schizophrenia are still unknown. For the last one hundred years, though, both “absent” and “perfect” vision have been associated with a lower risk for schizophrenia. Hence, vision itself and aberrations in visual functioning may be fundamental to the development and etiological explanations of the disorder. In this paper, we present the “Protection-Against-Schizophrenia” (PaSZ) model, which grades the risk for developing schizophrenia as a function of an individual’s visual capacity. We review two vision perspectives: (1) “Absent” vision or how congenital blindness contributes to PaSZ and (2) “perfect” vision or how aberrations in visual functioning are associated with psychosis. First, we illustrate that, although congenitally blind and sighted individuals acquire similar world representations, blind individuals compensate for behavioral shortcomings through neurofunctional and multisensory reorganization. These reorganizations may indicate etiological explanations for their protection against schizophrenia. Second, we demonstrate that visuo-cognitive impairments are fundamental for the development of schizophrenia. Deteriorated visual information acquisition and processing contribute to higher-order cognitive dysfunctions and subsequently to schizophrenic symptoms. Finally, we provide different specific therapeutic recommendations for individuals who suffer from visual impairments (who never developed “normal” vision) and individuals who suffer from visual deterioration (who previously had “normal” visual skills). Rather than categorizing individuals as “normal” and “mentally disordered,” the PaSZ model uses a continuous scale to represent psychiatrically relevant human behavior. This not only provides a scientific basis for more fine-grained diagnostic assessments, earlier detection, and more appropriate therapeutic assignments, but it also outlines a trajectory for unraveling the causes of abnormal psychotic human self- and world-perception.